2015
DOI: 10.21101/cejph.a4548
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Exacerbations and Symptom Variability in Children Due to Short-term Ambient Air Pollution Changes in Ostrava, Czech Republic

Abstract: SUMMARY Aim:The Ostrava region suffers from high levels of air pollution during winter inversions. We investigated the association between short-term elevations of air pollutant concentrations and worsening of respiratory problems, use of asthma medication and restriction of daily activities in asthmatic patients in Ostrava.Methods: One-hundred and forty-seven child and adolescent patients (aged 6-18 years) with a confirmed diagnosis of mild to moderate persistent asthma were included in the study. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Emerging trends in investigation of the biological properties of ET-1 and relevance of this vasoactive protein to cardiopulmonary disorders are driven substantially by recognition that this molecule is a critical factor in pathogenesis of diseases such as pulmonary arterial hypertension (PAH) (Kylhammar and Radegran 2016 ). Etiologic contributors to these diseases prominently include chronic exposure to aerial pollutants, in particular oxides of nitrogen and sulfur and partly combusted fuels (Cheng et al 2015 ; Velicka et al 2015 ; Ghanbari Ghozikali et al 2016 ). Public health policies in nations with severe air pollution problems, particularly the People’s Republic Of China, have responded to the burden placed on their medical care facilities by prioritizing support for research into ET-1 and other biomolecules that affect respiratory and cardiovascular function (Pan et al 2010 ; Luo et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging trends in investigation of the biological properties of ET-1 and relevance of this vasoactive protein to cardiopulmonary disorders are driven substantially by recognition that this molecule is a critical factor in pathogenesis of diseases such as pulmonary arterial hypertension (PAH) (Kylhammar and Radegran 2016 ). Etiologic contributors to these diseases prominently include chronic exposure to aerial pollutants, in particular oxides of nitrogen and sulfur and partly combusted fuels (Cheng et al 2015 ; Velicka et al 2015 ; Ghanbari Ghozikali et al 2016 ). Public health policies in nations with severe air pollution problems, particularly the People’s Republic Of China, have responded to the burden placed on their medical care facilities by prioritizing support for research into ET-1 and other biomolecules that affect respiratory and cardiovascular function (Pan et al 2010 ; Luo et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Studies in humans have also demonstrated moderately significant associations between the outdoor concentrations of PM 10 , SO 2 , and NO 2 and respiratory difficulties among asthmatic children and adolescents. 9 more cytotoxic and genotoxic than PM 2.5 in vitro. 10 Smaller PMs, which often have larger surface to volume ratio, may carry more toxins than larger particles, eventually having a greater health impact.…”
Section: ■ Introductionmentioning
confidence: 81%
“…U dorosłych pacjentów z przewlekłą obturacyjną chorobą płuc lub astmą oskrzelową już krótkotrwała ekspozycja na PM2,5 może nasilać objawy ze strony układu oddechowego i zmniejszać szczytowy przepływ wydechowy (PEF) [50,51]. W zależności od zastosowanego modelu iloraz szans wystąpienia objawów ze strony układu odde-chowego wynosił 1,22-1,57 przy wzroście stężenia PM2,5 o 50 µg/m 3 .…”
Section: Wpływ Filtracji Powietrza Na Przebieg I Objawy Chorób Alergi...unclassified